Energy Industry Performance in Saudi Arabia: Empirical Evidence - Aljaaidi, Khaled Salmen; Hassan, Waddah Kamal (International Journal of Energy Economics and Policy, 2020)
This study aims at investigating the associations of board of directors’ size, board of directors’ meetings, firm size and firm leverage with firm performance among energy industry in Saudi Arabia for periods ranging from 2005 to 2018. The final sample in this study consists of 56 observations. The ordinary-least square regression shows that board size is associated positively with firm performance. Further, the results of this study repot that board meetings, firm size and firm leverage are associated negatively with firm performance in the context of Saudi Arabia. The results of this study are important for policy makers at the country and corporate levels on issues related to corporate performance. Further, the results of this study can be used in future research to gain a deeper understanding of the issues of corporate performance. Keywords: Corporate Governance, Firm Size, Leverage and Performance, Energy Industry, Saudi Arabia JEL Classifications: G34, L25, P23 DOI: https://doi.org/10.32479/ijeep.9003